U.S. Sub-Prime Crisis: Origin and Causes - Sangeeta Sangeeta; Vinay Chamoli (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
The purpose of this paper is to explain the boom and bust of the housing market in the U.S. and how the sub-prime mortgages gave birth to new securitized products in the global economy. The majority of the researches conducted previously to explore the reason for the sub-prime crisis and its impact on the volatility on the stock market of the home country (U.S.) and the other developing countries. This paper also contributes to the literature about causes, timeline, and major crisis events during the crisis period. The literature on the Subprime crisis revealed many causes of the Sub-prime crisis. These were Imprudent Mortgage Lending, Housing Bubble, Global Imbalances, Securitization, Lack of Transparency and Accountability in Mortgage Finance, Rating Agencies- The credit rating agencies gave AAA ratings to numerous issues of subprime mortgage-backed securities, many of which were subsequently downgraded to junk status. Deregulatory Legislation, Government-Mandated Sub-prime Lending, Complexity of certain financial instruments, Failure of Risk Management Systems, Excessive Leverage and Relaxed Regulation of Leverage were the most discussed reasons of Subprime Crisis.